Edukasi Kesiapsiagaan Gempa Bumi pada Anak Berkebutuhan Khusus Menggunakan Media Pobody pada Siswa SLB Negeri 1 Lombok Barat [Earthquake Preparedness Education for Children with Special Needs Using Pobody Media at SLB Negeri 1 West Lombok] - Andrayani, Lale Wisnu; Kurnia, Theresia Avila; Taufiqurrahman, Taufiqurrahman (Indonesia Berdaya, 2025)
Abstract. Earthquakes are one of the disasters that frequently occur in Indonesia, such as the one that happened on Lombok Island in 2018. The series of earthquakes above 6 on the Richter Scale had a severe impact on the community, causing damage to residential homes and school buildings. One of the groups most affected during the disaster was children with disabilities. The damaged and collapsed school buildings, where children spend an average of seven hours a day, categorize schools as disaster-prone areas because a disaster can happen during school hours. Efforts to increase disaster preparedness often fail to involve children with disabilities, even though approximately 15% of the world's disaster victims are people with disabilities. Children with disabilities are vulnerable to becoming victims of a disaster due to a lack of understanding and preparedness. The purpose of this community service activity is to enhance the understanding of disaster preparedness among children with disabilities using a Pop-Up Book for Disability (POBODY) and videos. This activity was conducted at SLB Negeri 1 Lombok Barat in Dasan Geria village, West Lombok Regency, with a target audience of 30 special needs students. The activity was carried out through education using a Pop-Up Book for Disability (POBODY) and videos, followed by an evaluation of the results. The evaluation showed a significant increase in knowledge among the children with disabilities. Abstrak. Tata Kelola organisasi merupakan salah satu bentuk usaha organisasi dalam Menyusun dan mengorganisasikan kelompok atau usahanya. Dalam mencapai tata Kelola organisasi yang baik dapat terwujud dengan memanfaatkan sistem informasi akuntansi. Sistem informasi akuntansi berbasis website merupakan sistem yang dapat memberikan manfaat seperti transparansi, efisiensi, akuntabilitas, serta kemudahan dalam pelaporan dan audit. Pelaporan akuntansi dan keuangan di Pondok Pesantren Maahad Tahfiz Al-Quran Darul Falah Selangor Malaysia saat ini tata Kelola pondok pesantren masih menggunakan pencatatan laporan keuangan secara manual menggunakan buku.  Oleh karena itu tim pengabdian Masyarakat menawarkan untuk membantu mengelola organisasi berbasis sistem informasi akuntansi berbasis web. Sistem informasi akuntansi berbasis web diharapkan dapat membantu pondok pesantren dalam mengelola organisasi secara transparan cepat dan efisien. Hasil dari pengabdian Masyarakat ini menunjukkan bahwa pengelola pondok pesantren mampu mengoperasikan SIA secara mandiri setelah dilaksanakannya pelatihan, dan sudah mampu menerapkan prinsip tata Kelola organisasi lebih baik. Secara keseluruhan, kegiatan pengabdian masyarakat ini mampu memberikan dampak positif dalam memperkuat organsisasi, meningkatkan efisiensi operasional, serta mendorong pemanfaatan teknologi dalam mendukung keberlanjutan pondok pesantren